The relationship between safety and health with worker performances at Care Ion Technologist / Fathimatuzzahrah Mathar - Mathar, Fathimatuzzahrah (Faculty of Business and Management, 2011)
It is often suggested that in order for safety and health to positively influence worker performances. The purpose of the present study is to examine the relationship between safety and health with worker performances at Care Ion Technologist. Data were collected from 53 employees from 6 departments at Care Ion Technologist. Results from a survey of 53 employees showed that the relationship between safety and health with worker performances at Care Ion Technologist. Time consuming: Duration to complete this research is too short Limited resources - Occurs when the information gains from the respondent are not enough. Participation feedback - difficult to get responses and cooperation from them. This is because they have to carry out of their job. These results have important managerial implications: in order to obtain positive employee outcomes, organization should provide good safety and health in order to improve the worker performances. This study contributes to the knowledge on a study relationship safety and health with worker performances.